Website Sebagai Media Pelestarian Budaya Banyumas - Tyas Pratama Puja Kusuma; Debby Ummul Hidayah; Ely Purnawati (CV Nature Creative Innovation, 2024)
The purpose of this research is as follows: 1. To create a cultural preservation medium for Banyumas in the form of a Banyumas Culture website. 2. To encourage the wider community, especially the people of Banyumas, to preserve Banyumas culture and attract tourists to visit Banyumas. The research method applied in this study is the waterfall development method. The waterfall method consists of the following stages: Requirements analysis and definition, System and software design, Implementation and unit testing, Integration and system testing, Operation and maintenance. Based on the conducted research, the following conclusions can be drawn: 1. The Banyumas cultural preservation website provides information on the Banyumasan language dictionary, typical culinary information from Banyumas, tourism information in Banyumas regency, and local cultural information in Banyumas. 2. The Banyumasan language dictionary produces output in the form of Banyumasan language vocabulary in the Banyumas regional language dictionary. 3. The Banyumas cultural preservation website displays images/photos of typical Banyumas food and Banyumas culture, as well as navigation to tourist locations in the Banyumas region.